THE USE OF COCOA POD HUSK EXTRACT (THEOBROMA CACAO L.) AS AN EDIBLE COATING WITH THE ADDITION OF ALGINATE TO INCREASE THE SHELF LIFE OF TOMATOES (SOLANUM LYCOPERSICUM L.) - Rachmawaty, Miftahul Jannah, Nur Awalia, Hasri, Andi Munisa, Halifah Pagarra, Hartati (Chelonian Research Foundation, 2023)
This research aims to determine the effect of edible coating made from cocoa pod husk added with alginate-containing antimicrobials with different concentrations on the shelf life of tomatoes stored at 30o C and 4o C. Extraction of cocoa pod husk is carried out using the maceration method using acetone: water (7:3) solvent. Maserat underwent phytochemical screening. Edible coating made from cocoa pod husk extract with 10% concentration + 0% alginate; cocoa pod husk extract concentration 10% + alginate 1.5%; cocoa pod husk with 10% concentration + 2% alginate; and 10% concentration of cocoa pod husk extract + 2.5% alginate. Phytochemical test results show that cocoa pod husk extract contains phenolic compounds, flavonoids, alkaloids, and tannins. Edible coating cocoa pod husk extract 10% + 2% alginate had a significant effect on the weight loss of tomatoes, and cocoa pod husk extract 10% + 1.5% alginate had a significant effect on the pH of tomatoes in research on levels Vitamin C tomatoes are the best treatment for edible coating. Cocoa pod husk extract 10% + 2.5% alginate. The panelists' highest preference for tomatoes using edible coating was the treatment with cocoa pod husk extract + 2% alginate, storage temperature 30o C, and temperature 4o C with a rating of 4.0 (like). This research concludes that edible coatings based on cocoa pod husk extract with the addition of alginate can be used to package and extend the shelf life of tomatoes. Keywords: Alginate, Edible Coating, Cocoa Pod Husks Extract, Tomato Fruit